Referrals to the hospice service in Ireland - Phillips, Ceri; Neill, Susan (Economic & Social Studies, 1995)
The impact of demographic changes, resource constraints and the increase in demand for palliative care services require a clear understanding of the aims of the hospice movement, an insight into the perceptions of the referring agencies and details of the service recipients. A series of interviews and a postal survey of a sample of general practitioners were undertaken to establish the reasons underlying the referral of patients to the hospice service. The main reason for referral was palliation, although it was apparent that a number of factors, and their interrelationships, contributed to the decision-making process. The predominant view was that the hospice service provided an excellent service, although some concern was voiced at the emphasis given to cancer patients.
Keywords: Hospices; Health sector; Ireland; Palliative care services